DESIGN OF WORK EQUIPMENT SYSTEM AND STEAM SYSTEM WITH HYDRAULIC SYSTEM - Heri Wibowo (Jurnal Penelitian Saintek, 2004)
The weight  vehicle  was  used  to  work  the  weight job   of human  such as  digging    loading   and  lifting. the  materials    It  was  completed   bv system  work such  as attachment   svstem  and  driving  system.  The both of  system   must  he  supported    by  the  engine  follow    with  hydraulicsystem.    Design    0/  attachment     svst m    used    cylinder    hydraulicmovement  for  work 01 digging.  loading  or lifting.  and so do cylinder hydraulic   was  used  to  turning   all  bodv  of  vehicles.   The  movement and power  a/attachment    system  and  driving  system  was designed  to could  work  a/digging.    loading  and  lifiing.   The result  calculation   of attachment   force,    the   /ifi   hvdraulic    cylinder    is  designed    with   2cvlinders.   each  has   15 em  cvlinder   diameter   and   I  em  width   0/cylinder   with  uses  stainless   steel    (0.,    = 5100  kg/em'].   The  dump cylinder   is designed  with  I cvlinder.  has  /8  CI7I  ofcylinder  diameter and  I em  width  of cvlinder   with  lise the  same  materials.   Hydraulic svstem    uses   the   hydraulic    pump   to   central    work   of  attachment system  and driving  system  [hut drive from  engine  power.